Consumer Behaviour and Consumption practices towards less documented wild leafy Vegetables among Rural Households in Dodoma Region, Tanzania - Mbwana, Hadijah Ally (International Journal of Environment, Agriculture and Biotechnology, 2019)
Inadequate dietary diversity is a key challenge in many countries in sub-Saharan Africa. Diversifying diets with African indigenous vegetables is a sustainable way to supply a variety of nutrients to household members due to their richness in vitamins and minerals. Understanding the preferences and consumption practices of different varieties of wild vegetables is important information for agricultural promoters and is scarcely explored in Tanzania. This study aimed to gain an understanding of consumer behavior and consumption practices of wild vegetables in semi-arid areas in Tanzania in order to inform food policy and agricultural promoters. The study was conducted in two villages; Ilolo and Idifu from the semi-arid Dodoma region in Tanzania. Focus group discussions were conducted with forty women from both villages because women are more involved in cultivation, gathering and preparation of vegetables. Information collected in the focus group discussions included; perceptions, preferences, beliefs and taboos associated with consumption of wild vegetables. Participants reported that wild vegetables are seasonally available with most time of the year being scarce. The majority of the women reported consuming the wild vegetables due to good taste, abundance of nutrients, availability/affordability (they are mostly free), and because the other sources of relish are usually scarce. The most common wild vegetables that were consumed in the past 24 hours preceding the focus group discussions in the two villages included Ipomoea pandurate which is locally known as chiwandagulu and Corchorustrilocularis commonly known as ilende. For most vegetables, leaves and stems were common parts consumed. The women in both villages ranked Corchorustrilocularisas the most preferred wild vegetable. Women also reported some medicinal values attached to some of the wild vegetables such as BidensPilosa leaves which are claimed to increase blood. Generally, wild vegetables have the capability to escalate their significance to household income generation if farmers are given the chance to market them. Also domestication and promotion of these vegetables may help to enhance food and nutrition security.